2021
DOI: 10.1021/acs.jpcb.1c07902
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Effects on the Structural Dynamics of the Metal Ion–Crown Ether Complexes Investigated by Ultrafast Infrared Spectroscopy

Abstract: It is usually believed that the binding affinity and selectivity of an alkali metal ion with crown ether are defined by the size matching model. However, the underlying mechanism of the specific host−guest interactions and the structural dynamics of the metal ions confined in the cavity of the crown ethers in the solutions are still not clear. In this report, a series of alkali thiocyanate salts (XSCN; X = Li, Na, K, and Cs) complexed with 18-crown-6 (a typical crown ether) in the chloroform solutions were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Ultrafast infrared spectroscopy has been demonstrated to be a powerful technique to unravel the hydrogen bonding dynamics at a femtosecond time resolution in aqueous solutions. The specific host–guest interactions of crown ethers with metal cations and other host–guest complexes have been reported in previous studies. In this letter, the anion recognition dynamics between calix[4]­pyrroles and azide (N 3 – ) anions in the form of their tetrabutylammonium (TBA + ) and Na + salts was investigated in dimethyl sulfoxide (DMSO) solutions. The calix[4]­pyrroles were synthesized following the reported procedure, and the characterization data are given in the Supporting Information (Figures S1–S3).…”
mentioning
confidence: 98%
“…Ultrafast infrared spectroscopy has been demonstrated to be a powerful technique to unravel the hydrogen bonding dynamics at a femtosecond time resolution in aqueous solutions. The specific host–guest interactions of crown ethers with metal cations and other host–guest complexes have been reported in previous studies. In this letter, the anion recognition dynamics between calix[4]­pyrroles and azide (N 3 – ) anions in the form of their tetrabutylammonium (TBA + ) and Na + salts was investigated in dimethyl sulfoxide (DMSO) solutions. The calix[4]­pyrroles were synthesized following the reported procedure, and the characterization data are given in the Supporting Information (Figures S1–S3).…”
mentioning
confidence: 98%
“…43,47−49 It has also been pointed out that the cation that is selectively captured in the crown ethers' cavities has an explicit effect on the dynamics of these complexes. 56,57 The anhydrous supramolecular complex made up of 18-crown-6 and potassium hydrogen sulfate, 18-crown-6•KHSO 4 (1), was reported to undergo an enantiotropic solid−solid transition, which was believed, but never proved, to be associated with the onset of a dynamical process affecting the crown ether ligand and/or the hydrogen sulfate anion. 49 After almost 20 years, we finally gave insights into the genuine nature of such a transition, which leads to a superprotonic phase.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Crown ethers have been extensively studied in the past decades for their ability to coordinate alkali and various metal ions. Many studies on alkali metal cations coordinated to the crown ethers show how these supramolecular complexes are prone to undergoing one or more solid–solid phase transitions that may present dynamic features. , It has also been pointed out that the cation that is selectively captured in the crown ethers’ cavities has an explicit effect on the dynamics of these complexes. , The anhydrous supramolecular complex made up of 18-crown-6 and potassium hydrogen sulfate, 18-crown-6·KHSO 4 ( 1 ), was reported to undergo an enantiotropic solid–solid transition, which was believed, but never proved, to be associated with the onset of a dynamical process affecting the crown ether ligand and/or the hydrogen sulfate anion …”
Section: Introductionmentioning
confidence: 99%
“…For example, the complexation constant of 18-crown-6 to Ba 2+ is greater than that of K + in a methanol solution, while the complexation constant of dibenzo-18-crown-6 to K + is larger than that of Ba 2+ . 9 Recently, Zhou et al 26 proved the existence of 18-crown-6/ alkali metal ion complexes in chloroform and found that the structure and dynamics of metal ions in the complexes play an important role in the host−guest interaction. Thus, the recognition ability and binding stability of crown ethers to cations should be comprehensively considered from the sizematching degree between the crown ether cavity and the cation, the charge density of cations, the properties of anions, the degree of solvation, the temperature and pressure, the conformation of ligands, and the type of bonds formed in the complexes.…”
Section: Introductionmentioning
confidence: 99%